Bone Status Among Patients With Nonsurgical Hypoparathyroidism, Autosomal Dominant Hypocalcaemia, and Pseudohypoparathyroidism: A Cohort Study. (30th November 2017) - Underbjerg, Line; Malmstroem, Sofie; Sikjaer, Tanja; Rejnmark, Lars
ABSTRACT: Nonsurgical hypoparathyroidism (Ns‐HypoPT) and pseudohypoparathyroidism (PHP) are both rare diseases, characterized by hypocalcemia. In Ns‐HypoPT, PTH levels are low, whereas patients with PHP often have very high levels due to receptor‐insensitivity to PTH (PTH‐resistance). Accordingly, we hypothesized that indices of bone turnover and bone mineralization/architecture are similar in Ns‐HypoPT and PHP despite marked differences in PTH levels. We studied 62 patients with Ns‐HypoPT and 31 with PHP as well as a group of age‐ and sex‐matched healthy controls. We found a significantly higher areal BMD (aBMD) by DXA among patients with Ns‐HypoPT, both compared with PHP and the background population. Compared with Ns‐HypoPT, PHP patients had significantly lower total and trabecular volumetric BMD (vBMD) assessed by quantitative computed tomography (QCT) scans at the spine and hip. High‐resolution peripheral quantitative computed tomography (HRpQCT) scans showed a lower trabecular area and vBMD as well as a lower trabecular number at the tibia in PHP compared to Ns‐HypoPT and matched controls. In PHP, PTH levels correlated with levels of markers of bone formation (osteocalcin, bone‐specific alkaline phosphatase, P1NP), and bone resorption (CTx). In adult males, levels of bone markers were significantly higher in PHP compared with Ns‐HypoPT. Levels of procalcitonin and calcitonin were significantly higher in PHP compared with Ns‐HypoPT. In conclusion, indices of bone turnover, density, and microarchitecture differ between patients with Ns‐HypoPT and PHP. Our data suggest that patients with PHP do not have a complete skeletal resistance to PTH and that the effects of chronically high PTH levels in PHP are mostly confined to the trabecular tissue. © 2017 American Society for Bone and Mineral Research.